Effects of Web-based education model on knowledge regarding reproductive and sexual health among pre-marital couple in West Sumatra Province Indonesia: A Feasibily Study - Hasrah Murni; Darmayanti Y; Arneti Arneti (Publikasi Indonesia, 2023)
Design: A quasi experimental design with two group pre test-post test was conducted in the population of premarital couple in Bukittinggi City West Sumatera Province Indonesia from January to December 2021. All particiapnts received Web-based education method named RHAPS focused on sexual and reproductive health. The participants invited to complete the intervention during the marital registration process using an individualised log-in process. A random sample of 60 persons was selected. Data collection was done in 5 stages, namely media needs analysis, expert test, small scale test, small scale test and website effectiveness test. Data were collected by a questionnaire used in two stages of pre and post program implementation. Results: The results of the feasibility test by media and material experts showed the S-CVI score was .83. The acceptability of the RHAPS showed 85,5% of the participants were very agree to use the website model. The average pre-test and post score regarding knowledge about sexual and reproductive health of the participants in the intervention group showed significant difference after received the program (p< .05). Conclusion & recommendations: Premarital education program was successful in attaining its aim of positively changing the knowledge regarding sexual and reproductive health. The RHAPS model can be used as a medium in the implementation of sexual and reproductive health for future brides